Measuring the dark core of personality in Portugal: a psychometric examination of D - Pechorro, Pedro Fernandes dos Santos (Deviant behavior, 2024)
The dark core of personality is a recently developed construct that encompasses the malevolent, antagonistic, and aversive side of human nature. The aim of the present study is to examine the psychometric properties of the dark core of personality D measure, namely D70, and its two shorter versions, D35 and D16, in Portugal. Two samples of Portuguese participants were used in the current study (N = 570, M = 35.42 years, SD = 11.41, range = 18-69; N = 242, M = 30.19 years, SD = 12.78, range = 16-77). The one-factor models of the D70, D35, and D16 obtained adequate fits, but the bifactor and second-order models of the D70 were less than satisfactory. Internal consistency/reliability, as measured by the alpha and omega coefficients and more traditional indicators, was very good. Convergent validity, and criterion-related validity (with trouble with the law, arrested by police, sentenced to prison, and alcohol/drug abuse variables) were demonstrated. Cross-gender and cross-age measurement invariance was established, with males and younger participants scoring significantly higher. The findings provide some support for the use of the D as a valid and reliable measure of the dark core of the personality construct.